In vivo confirmation of the reliability of the dorsal tangential view of the wrist - (:unkn) unknown (ELSEVIER, 2018)
The purpose of the study was to evaluate the reliability of the dorsal tangential view (DTV) of the wrist using direct visualization of the extensor compartments in vivo. Twelve patients with extensor tendon complications [nine patients with extensor synovitis, two patients with isolated extensor pollicis longus (EPL) rupture, one patient with EPL and extensor indicis proprius rupture] after volar plating of a distal radius fracture were enrolled in the study. We obtained DTVs in the operating room before implant removal and explored the extensor compartments during synovectomy or tendon reconstruction to confirm suspected screw penetration. We confirmed screw penetration on 10 patients during exploration of the extensor compartments. DTV was able to detect seven of these dorsal cortex breaches. There were no false positive results, which we had defined as a screw penetrating an extensor compartment preoperatively, but not visible on the DTV. Of these seven breaches, one was in the second compartment, four were in the third compartment, and the remaining two were in the fourth compartment. The DTV is sufficiently reliable to be used routinely to reduce postoperative extensor tendon complications during volar plating of the distal radius. Level of evidence: 4 (case series) diagnostic. (C) 2017 SFCM. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Dorsal tangential view; Distal radius fracture; Extensor tendon; Complication; Screw penetration; Rupture; Attrition; DISTAL RADIUS FRACTURES; POLLICIS LONGUS TENDON; VOLAR LOCKING PLATES; SCREW PENETRATION; EXTENSOR TENDON; DELAYED RUPTURE; FIXATION; TOMOGRAPHY; TUBERCLE; DETECT